Pharmaceutical intervention for adverse events improves quality of life in patients with cancer undergoing outpatient chemotherapy - Hironori Fujii; Yukino Ueda; Chiemi Hirose; Koichi Ohata; Kumiko Sekiya; Mika Kitahora; Shiori Sadaka; Senri Yamamoto; Daichi Watanabe; Hiroko Kato-Hayashi; Hirotoshi Iihara; Ryo Kobayashi; et al. (BMC, 2022)
Abstract Background The effect of pharmaceutical intervention to treat adverse events on quality of life (QOL) in outpatients receiving cancer chemotherapy is unclear. We investigated whether pharmaceutical intervention provided by pharmacists in collaboration with physicians improves QOL with outpatient cancer chemotherapy. Methods We conducted a single-center retrospective descriptive study of pharmaceutical intervention for patients receiving outpatient cancer chemotherapy at Gifu University Hospital between September 2017 and July 2020. We assessed patient QOL using the Japanese version of the EuroQol 5 Dimension5 Level (EQ-5D-5L). Adverse events were graded using the Common Terminology Criteria for Adverse Events (CTCAE) version 4.0. We compared the EQ-5D-5L utility value and incidence of grade 2 or higher adverse events before and after pharmaceutical intervention. Results Our analysis included 151 patients who underwent 210 chemotherapy cycles. Pharmaceutical intervention significantly improved patients' EQ-5D-5L utility values from 0.8197 to 0.8603 (P < 0.01). EQ-5D-5L utility values were significantly improved after pharmaceutical intervention for nausea and vomiting (pre-intervention 0.8145, post-intervention 0.8603, P = 0.016), peripheral neuropathy (pre-intervention 0.7798, post-intervention 0.7988, P = 0.032) and pain (pre-intervention 0.7625, post-intervention 0.8197, P = 0.035). Although not statistically significant, the incidence of grade 2 or higher adverse events, including nausea and vomiting, dermopathy, pain, oral mucositis, diarrhea and dysgeusia, tended to be lower post-intervention than pre-intervention. Conclusions Pharmaceutical intervention by pharmacists in collaboration with physicians may improve QOL in patients undergoing outpatient cancer chemotherapy.